Representasi Gender dalam Buku BIPA 7 Seri Pelajar “Sahabatku Indonesia” - Denda Rinjaya (Badan Pengembangan dan Pembinaan Bahasa, 2020)
Gender bias in textbook material affects learners in learning language. The purpose of this research is to reveal the gender representation in the BIPA 7 Learners Series “Sahabatku Indonesia”. Content analysis is carried out on the textual and visual material contained in the book. The results of this study reveal that the male character representation is more dominant than the female textually. Based on their social roles, male characters in textual materials are more diverse than characters that represent women. In addition, the results of the analysis of visual material in the form of pictures, photographs and illustrations also show the dominance of men over women with a ratio of 4: 1. In conclusion, the material contained in the analyzed books has not provided equal opportunities between women and men in Indonesian language teaching materials for foreigners.